Limiting dynamics of high-frequency electromechanical transduction of outer hair cells - Frank, Gerhard (The National Academy of Sciences, 1999)
High-frequency resolution is one of the salient features of peripheral sound processing in the mammalian cochlea. The sensitivity originates in the active amplification of the travelling wave on the basilar membrane by the outer hair cells (OHCs), where electrically induced mechanical action of the OHC on a cycle-by-cycle basis is believed to be the crucial component. However, it is still unclear if this electromechanical action is sufficiently fast and can produce enough force to enhance mechanical tuning up to the highest frequencies perceived by mammals. Here we show that isolated OHCs in the microchamber configuration are able to overcome fluid forces with almost constant displacement amplitude and phase up to frequencies well above their place-frequency on the basilar membrane. The high-frequency limit of the electromotility, defined as the frequency at which the amplitude drops by 3 dB from its asymptotic low-frequency value, is inversely dependent on cell length. The frequency limit is at least 79 kHz. For frequencies up to 100 kHz, the electromotile response was specified by an overdamped (Q = 0.42) second-order resonant system. This finding suggests that the limiting factor for frequencies up to 100 kHz is not the speed of the motor but damping and inertia. The isometric force produced by the OHC was constant at least up to 50 kHz, with amplitudes as high as 53 pN/mV being observed. We conclude that the electromechanical transduction process of OHCs possesses the necessary high-frequency properties to enable amplification of the travelling wave over the entire hearing range.